Long-term prognostic role of diabetes mellitus and glycemic control in heart failure patients with reduced ejection fraction: Insights from the MECKI Score database. (15th October 2020) - Paolillo, Stefania; Salvioni, Elisabetta; Perrone Filardi, Pasquale; Bonomi, Alice; Sinagra, Gianfranco; Gentile, Piero; Gargiulo, Paola; Scoccia, Alessandra; Cosentino, Nicola; Gugliandolo, Paola; Badagliacca, Roberto; Lagioia, Rocco; et al.
Abstract: Background: The prognostic role of diabetes mellitus (DM) in heart failure (HF) patients is undefined, since DM is outweighed by several DM-related variables when confounders are considered. We determined the prognostic role of DM, treatment, and glycemic control in a real-life HF population. Methods: 3927 HF patients included in the Metabolic Exercise Cardiac Kidney Index (MECKI) score database were evaluated with a median follow-up of 3.66 years (IQR 1.70–6.67). Data analysis considered survival between DM ( n = 897) vs. non-DM ( n = 3030) patients, and, in diabetics, between insulin ( n = 304), oral antidiabetics ( n = 479), and dietary only ( n = 88) treatments. The role of glycemic control was evaluated grouping DM patients according to glycated hemoglobin (HbA1c): <7% ( n = 266), 7.1–8% ( n = 133), >8% ( n = 149). All analyses were performed also adjusting for ejection fraction, renal function, hemoglobin, sodium, exercise peak oxygen uptake, and ventilation/carbon dioxide relationship slope. Study primary endpoint was the composite of cardiovascular death, urgent heart transplantation, or left ventricular assist device implantation. Secondary endpoints were cardiovascular and all causes death. Results: For all endpoints, upon adjustment for confounders, DM status and insulin treatment or dietary regimen were not significantly associated with adverse long-term prognosis compared to non-DM and oral antidiabetic treated patients, respectively. A worse prognosis was observed in HbA1c >8% patients (Log-Rank p < 0.001), even after correction for confounding factors. All results were replicated by hazard ratio analysis. Conclusion: In HF patients, DM, insulin treatment and dietary regimen are not adverse outcome predictors. The only condition related to long-term prognosis, considering potential confounders, is poor glycemic control. Graphical abstract: Unlabelled Image Highlights: This is a new point of view in the prognostic assessment of HF diabetic patients. Considering patients with diabetes mellitus as a unique group could be not correct. Single and specific disease-related parameters participate to long-term prognosis. Individual disease variability overcomes the importance of the disease per se.